2019
DOI: 10.1093/cdn/nzz116
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of Infrared Analyzers for Measuring Human Milk Macronutrients in a Milk Bank Setting

Abstract: BackgroundInfrared (IR) analysis is an emerging technology that may be a useful tool for milk banks to manage the nutrient variability in donor human milk.ObjectiveTo evaluate the accuracy, reliability, and comparability of commercial infrared analyzers for measuring human milk macronutrients in a milk bank setting.MethodsThree nonprofit milk banks received blinded test kits of human milk that had been assessed using reference methods. Four infrared instruments were used to measure macronutrients as follows: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The most common analytical method used for measuring macronutrients in the studies reviewed was infrared analysis. A growing body of evidence suggests that infrared analysis can reliably measure total nitrogen (e.g., crude protein) and fat in human milk, with appropriate sample handling and instrument calibration, though measurements of lactose were less accurate, and the measurement of total carbohydrates in human milk has not been validated (36)(37)(38)(39)(40)(41)(42) . None of the reviewed studies used reference methods suggested by the USDA (8) to measure total protein or total fat, and only 1 study used reference methods for measuring lactose, which limits the ability to draw conclusions about actual nutrient ranges.…”
Section: Methodsmentioning
confidence: 99%
“…The most common analytical method used for measuring macronutrients in the studies reviewed was infrared analysis. A growing body of evidence suggests that infrared analysis can reliably measure total nitrogen (e.g., crude protein) and fat in human milk, with appropriate sample handling and instrument calibration, though measurements of lactose were less accurate, and the measurement of total carbohydrates in human milk has not been validated (36)(37)(38)(39)(40)(41)(42) . None of the reviewed studies used reference methods suggested by the USDA (8) to measure total protein or total fat, and only 1 study used reference methods for measuring lactose, which limits the ability to draw conclusions about actual nutrient ranges.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ultra-high-performance LC–tandem MS (UHPLC–MS/MS) and inductively coupled plasma–atomic emission spectrometry coupled with a mass spectrometer (ICP–MS) are now optimized for the analysis of a panel of B vitamins (vitamin B-1, B-2, B-3, and B-6) and minerals (iron, copper, zinc, iodine, calcium, and magnesium), respectively ( 75 , 76 ). Also, a human-milk analyzer based on mid- and near-infrared spectroscopy has been developed to simultaneously measure all macronutrients ( 77 , 78 ).…”
Section: Advances and Technologies For Human-milk Analysismentioning
confidence: 99%
“…Recent research has shown that a variety of infrared analyzers are reliable and accurate for measuring fat and protein in a milk bank setting. 32 Fu et al 8 examined the macronutrients in target pooled DHM from one milk bank and reported fat values from 1.5 to 4.5 g/dL, and protein values from 0.3 to 1.4 g/dL. In our study, we observed higher minimum values in target pooled milk (2.6 g/dL for fat and 0.8 g/dL for protein) than those reported by Fu et al These differences may be related to sample collection protocol.…”
Section: Impact Of Target Poolingmentioning
confidence: 99%